Structural analysis of nanostructured iron antimonate by experimental and quantum chemical simulation and its LPG sensing - Singh S.; Gupta V.; Yadav B.C.; Tandon P.; Singh A.K. (My University, 2025)
In this paper structural, electrical, magnetic as well as liquefied petroleum gas (LPG) sensing properties of the synthesized ultrafine iron antimony oxide along with quantum chemical simulation have been reported. A detailed study of the structural analysis is presented including a thorough Raman spectroscopy and infra-red investigations. A detailed vibrational analysis of iron antimony oxide was performed by ab-initio Hartree-Fock (HF) and density functional theory (DFT) employing B3LYP exchange correlation functional with LanL2DZ and 6-311++G(d,p) basis sets. The observed spectral patterns were compared and assigned with fundamental vibrational frequencies showing an overall excellent agreement. X-ray diffraction along with Rietveld analysis was used to confirm the crystal structure, space group and crystallite size. The estimated value of minimum crystallite size was found 2 nm and confirmed by Rietveld and Vibrational spectral analysis. Scanning electron microscopy, Elemental mapping and Energy dispersive X-ray analysis were applied for surface morphology, elemental distributions and compositions of the material, respectively. The synthesized nanoparticles were used for the processing of gas-sensing device and the outstanding gas-sensing properties are accessible, proving the effectiveness of the whole process in advancing toward a new generation of gas-sensor. © 2014 Elsevier B.V.